The Leadership Performance of Social Workers in Human Services Organizations: Competency Analysis of the Head of the Research and Program Development (RPD) Department of Rumah Zakat Bandung - Aliim, Tahrizi Fathul; Nulhaqim, Soni Akhmad; Darwis, Rudi Saprudin (Universitas Padjadjaran, 2025)
Leadership in human services organizations, such as Rumah Zakat Bandung, plays a crucial role in ensuring the effectiveness and sustainability of programs. Effective leadership includes the ability to motivate teams, manage resources, and adapt to ever-changing social and economic dynamics. This study, employing a qualitative approach with a case study design, explores the role of the Head of the Research and Program Development (RPD) Department in fostering a positive work environment and empowering team members as the primary implementers of programs. Using leadership frameworks (Healy, Covey, Senge, and Skidmore), the findings reveal that a leader's positive attitude and recognition of team contributions enhance motivation, engagement, and commitment to the organization’s mission. This results in improved individual and team performance, as well as better service quality for the community. Through close collaboration, effective communication, and ongoing capacity development, the Head of the RPD Department ensures that Rumah Zakat Bandung remains adaptive and efficient in addressing community needs while maintaining its reputation as a professional and trusted human services organization.